Da condução das almas ao governo da população: analítica do processo de constituição da noção de governamentalidade na obra de Michel Foucault - Souza, Washington Luis (2012)
The choice of an object of study within the philosophical trajectory of Michel Foucault requires some caution. When it comes to thinking about his works, explanations about options taken, clarification of the demarcations relative to his entire writings, internal division delimitations in the outlined periods and in the chosen works are necessary. So, a moment of his intellectual path, named genealogical, comes into our focus. Within this period, we will focus on the research carried out between 1976 and 1979, specifically the themes dealt with in Michel Foucault's lectures ministered at Collège de France: The Birth of Biopolitics and "Security, territory, population". In the set of various possible thematic axes that these lectures can give rise to, this paper aims to present a reading in perspective aiming to delineate, from a political framework, the development lines of governmentalization concept and its entanglement with the diverse political-institutional formation related to the constitution of what Foucault calls Modern governmentalized state . Therefore, the different models of governmentality studied by Foucault will be analyzed in this paper. These different models are: the ancient way of governmentality that can be found in the pastoral power; the modern governmental rationality put in work between the sixteenth and the eighteenth century by the reason of State and the liberal configuration of governmentality conceived in the middle of the eighteenth century to its contemporaneous neoliberal inflections which can be exemplified by the German and North American models in the middle of the twentieth century